2020
DOI: 10.1093/pasj/psaa036
|View full text |Cite
|
Sign up to set email alerts
|

The Seimei telescope project and technical developments

Abstract: An overview of the Seimei telescope, a 3.8 m optical infrared telescope located on Mt. Chikurinji in the Okayama prefecture of Japan, is presented. Seimei is a segmented-mirror telescope whose primary mirror consists of 18 petal-shaped segments. The telescope tube supporting the thin segmented mirrors is structurally incorporated within large arc-rails providing the elevation axis. The tube has a light-weight homologous structure designed with a genetic algorithm. The total weight of the telescope tube, includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 15 publications
0
30
0
Order By: Relevance
“…We conducted optical spectroscopic and photometric monitoring observations of the young solar-type star EK Dra from February to April 2020. The spectroscopic data were obtained by the 3.8-m Seimei telescope (Kurita et al 2020) (see Section 2.2) and photometric data were obtained by Transiting Exoplanet Survey Satellite (TESS ; Ricker et al 2015) (see Section 2.1). Through this campaign, we succeeded in obtaining optical spectroscopic data of two superflares on a solar-type star, simultaneously with TESS photometry.…”
Section: Observations and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted optical spectroscopic and photometric monitoring observations of the young solar-type star EK Dra from February to April 2020. The spectroscopic data were obtained by the 3.8-m Seimei telescope (Kurita et al 2020) (see Section 2.2) and photometric data were obtained by Transiting Exoplanet Survey Satellite (TESS ; Ricker et al 2015) (see Section 2.1). Through this campaign, we succeeded in obtaining optical spectroscopic data of two superflares on a solar-type star, simultaneously with TESS photometry.…”
Section: Observations and Analysismentioning
confidence: 99%
“…We introduce the utilization of low-resolution spectroscopic data from KOOLS-IFU (Kyoto Okayama Optical Lowdispersion Spectrograph with optical-fiber Integral Field Unit; Matsubayashi et al 2019) installed at the 3.8-m Seimei Telescope (Kurita et al 2020) at Okayama Observatory of Kyoto University. KOOLS-IFU is an optical spectrograph with a spectral resolution of R ∼ 2,000 covering a wavelength range from 5800-8000 Å, including the Hα line (6562.8 Å).…”
Section: 8-m Seimei Telescopementioning
confidence: 99%
“…Bright spotted stars have been observed by TESS (Ricker et al 2014), and superflares on hundreds of spotted solar-type stars have been reported (Feinstein et al 2020;Tu et al 2020). Some TESS targets are to be simultaneously observed by the Seimei telescope at Kyoto University (Kurita et al 2020) using the high dispersion spectrograph. This could allow us to obtain informative prior knowledge for conducting starspot modeling of TESS data.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…In Japan, Kyoto University has developed Seimei telescope which is the largest in East Asia [2,3]. Keck telescopes and their copies are the unique segmented primary mirror telescopes which are equipped with the segmented mirror control system [4], and Seimei telescope is essentially the second one in the world.…”
Section: Introductionmentioning
confidence: 99%
“…Seimei telescope is therefore the first petal-type in the world. The development process and specifications of Seimei telescope and the comparisons with conventional segmented telescopes are summarized in [3].…”
Section: Introductionmentioning
confidence: 99%